2021
DOI: 10.14195/1647-8606_64-1_6
|View full text |Cite
|
Sign up to set email alerts
|

Validação da Career-Related Parent Support Scale numa amostra de estudantes portugueses

Abstract: A Career Related Parent Support Scale (CRPSS) procura avaliar, de acordo com as principais fontes de autoeficácia, o suporte parental percebido, em quatro dimensões: modelação de carreira, suporte emocional, apoio instrumental, e persuasão verbal. No presente estudo, tivemos como objetivo apresentar os principais resultados do processo de tradução e de adaptação à população portuguesa da CRPSS, com uma amostra de 338 estudantes dos ensinos básico e secundário. Globalmente, os resultados das análises realizadas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 0 publications
4
4
0
Order By: Relevance
“…Indeed, in intentional and goal-directed actions, such as career exploration activities, emotions may have a self-regulatory function in information-seeking behaviors ( Young et al, 2002 ). In this regard, it should be noted that the results observed in the studies by Lee et al (2016) and, more recently, Gamboa et al (2021) corroborate the assumptions of Blustein (1988) and Flum and Blustein (2000) , who describe exploration as a goal-oriented process. Thus, research is needed to analyze the role of the processes that initiate, cease, sustain, and guide career exploration.…”
Section: Introductionsupporting
confidence: 73%
See 3 more Smart Citations
“…Indeed, in intentional and goal-directed actions, such as career exploration activities, emotions may have a self-regulatory function in information-seeking behaviors ( Young et al, 2002 ). In this regard, it should be noted that the results observed in the studies by Lee et al (2016) and, more recently, Gamboa et al (2021) corroborate the assumptions of Blustein (1988) and Flum and Blustein (2000) , who describe exploration as a goal-oriented process. Thus, research is needed to analyze the role of the processes that initiate, cease, sustain, and guide career exploration.…”
Section: Introductionsupporting
confidence: 73%
“…Cronbach’s alpha for the Portuguese version ranged from 0.63 to 0.83. Research that used this version found internal consistency values for the two exploration processes used in this study between 0.74 and 0.79 ( Paixão and Gamboa, 2017 , 2022 ; Gamboa et al, 2021 ) and we obtained values of 0.80 for environmental exploration and 0.76 for self-exploration.…”
Section: Methodssupporting
confidence: 52%
See 2 more Smart Citations
“…The perceived parental support was assessed with the Career-Related Parent Support Scale (CRPSS, Turner et al, 2003 ; adapt. Gamboa et al, 2021 ). It aims to assess students’ perceptions of parental support toward career and educational development along the four sources of self- efficacy expectations proposed by Bandura (1997) .…”
Section: Methodsmentioning
confidence: 99%